2018
DOI: 10.1038/s41467-018-06513-6
|View full text |Cite
|
Sign up to set email alerts
|

A sustained change in the supply of parental care causes adaptive evolution of offspring morphology

Abstract: Although cooperative social interactions within species are considered an important driver of evolutionary change, few studies have experimentally demonstrated that they cause adaptive evolution. Here we address this problem by studying the burying beetle Nicrophorus vespilloides. In this species, parents and larvae work together to obtain nourishment for larvae from the carrion breeding resource: parents feed larvae and larvae also self-feed. We established experimentally evolving populations in which we vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 52 publications
(56 reference statements)
4
66
1
Order By: Relevance
“…; Jarrett et al. ). The facultative nature of posthatching parental care makes this an excellent species in which to examine the effect of parental care on the expression and maintenance of phenotypic variation (Smiseth et al.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…; Jarrett et al. ). The facultative nature of posthatching parental care makes this an excellent species in which to examine the effect of parental care on the expression and maintenance of phenotypic variation (Smiseth et al.…”
Section: Methodsmentioning
confidence: 98%
“…Although parents in this treatment were not forced to provide care to their larvae, previous work has shown that under these conditions the parents care for the brood for at least the first 24 hours after hatching (Jarrett et al. ), which is the time period during which parental care is most beneficial to larvae (Eggert et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…This cooperative effort is probably achieved through multiple sets of mandibles working simultaneously on the carcass (Jarrett et al ., in press [31]). Larvae that fail in this task die within 8 h of hatching [24].…”
Section: Discussionmentioning
confidence: 99%
“…In many altricial systems, offspring evolve reduced size in structures that promote independence (Derrickson, ; Nalepa et al, ; Nice, ; O'Reilly et al, ; Ricklefs, ; Werneburg et al, ). Here, we expected independent larvae that might need to self‐feed to have larger mandibles, as mandible size is correlated to feeding ability is observed in other insects (Bernays, ) and larvae of the facultative species N. vespilloides have evolved larger mandibles during experimental adaptation to the absence of parental care (Jarrett et al, ). However, for the two species examined here, we found no such trend.…”
Section: Discussionmentioning
confidence: 99%
“…We focus our attention on the mandible, which is the primary feeding tool for many insects (Chapman & de Boer, ) and is frequently associated with variations in feeding performance (Bernays, ; Hochuli, ). Furthermore, experimental populations of third instar N. vespilloides larvae were recently found to evolve larger mandibles in the absence of parental care, suggesting a role for mandibles in self‐feeding ability (Jarrett et al, ). Specifically, we predicted that the mandibles of first instars of obligate care species would display markedly different morphology from all other larvae, as their evolution should be unconstrained by the need to self‐feed.…”
Section: Introductionmentioning
confidence: 99%